Thauma: Pain or Wonder?: Considerations Starting from Emanuele Severino and Martin Heidegger (Thauma: ¿Dolor o maravilla? Consideraciones a partir de Emanuele Severino y Martin Heidegger) - Tarquini, Nicolò (Cauriensia, 2023)
The topic of evil, variously understood, constitutes a fundamental object of questioning and problematicity, so much so that the Italian philosopher Emanuele Severino believes that the thauma from which philosophical research traditionally begins means precisely "anguished pain", caused, in the last resort, from the becoming of entities. This article intends, first of all, to evaluate the argumentative cogency of the Severinian interpretation in reference to this/of this question and then, move on to analyze some of the writings in which Martin Heidegger deals with the same theme/subject: even the German philosopher has in fact provided interesting considerations that can be profitably used to grasp the most appropriate way of understanding this concept. The question that arises, in fact, is not purely terminological, but involves the same intonation that characterizes the philosophical question and the starting point from which it originates. From the comparison between the two philosophers, in addition to some interpretative limits that seem to be found in both, some significant convergences will emerge, at least in relation to the role that emotions play within the philosophical investigation.